Time-dependent network algorithm for ranking in sports - London András; Németh József; Németh Tamás; Symposium on Programming Languages and Software Tools (2013) (Szeged) (2014)
In this paper a novel ranking method which may be useful in sports like tennis, table tennis or American football, etc. is introduced and analyzed. In order to rank the players or teams, a time-dependent PageRank based method is applied on the directed and weighted graph representing game results in a sport competition. The method was examined on the results of the table tennis competition of enthusiastic sport-loving researchers of the Institute of Informatics at the University of Szeged. The results of our method were compared by several popular ranking techniques. We observed that our approach works well in general and it has a good predictive power.
Keywords: Természettudományok; Számítás- és információtudomány